2009
DOI: 10.4049/jimmunol.0804328
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoregulatory Enzyme IDO Paradoxically Drives B Cell-Mediated Autoimmunity

Abstract: Rheumatoid arthritis (RA) is a chronic and debilitating inflammatory autoimmune disease of unknown etiology. As with a variety of autoimmune disorders, evidence of elevated tryptophan catabolism has been detected in RA patients indicative of activation of the immunomodulatory enzyme IDO. However, the role that IDO plays in the disease process is not well understood. The conceptualization that IDO acts solely to suppress effector T cell activation has led to the general assumption that inhibition of IDO activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(130 citation statements)
references
References 57 publications
6
122
1
1
Order By: Relevance
“…In sharp contrast, IDO can act as a mediator of inflammatory disease, particularly in ischemia-reperfusion injury (20). Additionally, it was reported that administration of 1-MT to K/BxN mice reduced the level of inflammatory cytokines and autoantibodies, resulting in an attenuated course of arthritis (21). Thus, IDO has contrasting effects on several types of inflammation models.…”
Section: Discussionmentioning
confidence: 99%
“…In sharp contrast, IDO can act as a mediator of inflammatory disease, particularly in ischemia-reperfusion injury (20). Additionally, it was reported that administration of 1-MT to K/BxN mice reduced the level of inflammatory cytokines and autoantibodies, resulting in an attenuated course of arthritis (21). Thus, IDO has contrasting effects on several types of inflammation models.…”
Section: Discussionmentioning
confidence: 99%
“…The role of B cells and autoimmunity as factors that contribute to neurological outcomes following SCI is poorly understood. The alteration of the local cytokine environment during SCI favors B-cell autoimmunity [57], and B cells produce pathogenic antibodies that impair lesion repair [58], resulting in worse neurological outcome. Therapies that target the B cell or obstruct the effects of pathogenic antibodies have demonstrated to be effective [20,59].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, part of O2 ‱-generated during mitochondrial electron transfer is vectorially released into the intermembrane space [78]. The mechanism underlying the release of O2 ‱-into the intermembrane space covers the formation of ubisemiquinone at two sites in the ubiquinone pool: the Q1 site that lies near the matrix, and the Qo site in the vicinity of the intermembrane space [154]. Autooxidation of ubisemiqiunone at the Qo site (UQo ‱-) results in the release of O2 ‱-through the cytosolic side of the mitochondrial inner membrane.…”
Section: Mitochondrial Respirationmentioning
confidence: 99%